Cultural journeys in higher education : student voices and narratives - Bamford, Jan; Pollard, Lucie (Great debates in higher education., 2019)
The cultural diversity of university student populations can be seen to reflect the changing demographics of an increasingly international mobile workforce. The implications of the growing migrant population and differing communication patterns in the classroom is a highly under-researched area. Cultural Journeys in Higher Education provides a unique insight into the cultural experiences of university recounted through the students' narratives and voices.This book explores the increasingly culturally diverse composition of the student body and its impact on student learning. The need to negotiate differing cultural scripts and adapting to the new cultural landscape when students arrive at university are just a few of the experiences addressed within this important text. Cultural Journeys in Higher Education navigates the issue of curriculum delivery through the eyes of those who receive the education and questions whether a new approach is needed to adapt to an increasingly culturally diverse student body. The student experience is a central focus of this book, giving researchers, practitioners and leaders in education a unique perspective that will enable them to further understand the cultural framework that underpins Higher Education.